2010
DOI: 10.1074/jbc.m109.092916
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glucose-6-phosphate Dehydrogenase Promotes Acute Hypoxic Pulmonary Artery Contraction

Abstract: Hypoxic pulmonary vasoconstriction (HPV) is a physiological response to a decrease in airway O 2 tension, but the underlying mechanism is incompletely understood. We studied the contribution of glucose-6-phosphate dehydrogenase (Glc-6-PD), an important regulator of NADPH redox and production of reactive oxygen species, to the development of HPV. We found that hypoxia (95% N 2 , 5% CO 2 ) increased contraction of bovine pulmonary artery (PA) precontracted with KCl or serotonin. Depletion of extracellular glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 49 publications
5
49
0
Order By: Relevance
“…The pentose phosphate pathway is also oxygen sensitive. In coronary arterial smooth muscle, the pentose phosphate pathway activity is decreased by reductions in PO 2 (21), but in the pulmonary arterial smooth muscle (10,18) and in solid tumors (15) the activity is increased by hypoxia. Similarly, we found that G6PD activity is enhanced in hypoxic CD133…”
Section: Pluripotent Cd133mentioning
confidence: 99%
See 1 more Smart Citation
“…The pentose phosphate pathway is also oxygen sensitive. In coronary arterial smooth muscle, the pentose phosphate pathway activity is decreased by reductions in PO 2 (21), but in the pulmonary arterial smooth muscle (10,18) and in solid tumors (15) the activity is increased by hypoxia. Similarly, we found that G6PD activity is enhanced in hypoxic CD133…”
Section: Pluripotent Cd133mentioning
confidence: 99%
“…In addition, TGF-␤ upregulates glucose-6-phosphate dehydrogenase (G6PD) expression in fetal brown adipocytes and increases levels of NOX4-derived ROS (45). Because production of superoxide anion from NOX is dependent on G6PD-derived NADPH (18,20), we hypothesized that increases in G6PD-dependent NA-DPH redox and NOX-derived ROS act in concert to mediate hypoxia-induced CD133 ϩ cell expansion and differentiation. …”
mentioning
confidence: 99%
“…G6PD inhibition relaxes pulmonary arteries by decreasing intracellular calcium (20), prevents switching of vascular smooth muscle cells to a synthetic phenotype (9,10), and reduces pulmonary hypertension (9,47). However, whether prolonged hypoxia-induced 20-HETE-synthesis is G6PD dependent or independent and whether G6PD modulates 20-HETE signaling in the vascular smooth muscle remain unknown.…”
Section: -Hydroxyeicosatetraeonic Acid (20-hete) Plays a Critical Rmentioning
confidence: 99%
“…Endothelium denuded artery rings were mounted on Radnoti Instruments' force displacement transducers for recording isometric force development through Powerlab data acquisition system from AD Instruments, as previously described (20). Arterial rings were incubated in Krebs-bicarbonate buffer containing 118 mM NaCl, 4.7 mM KCl, 1.5 mM CaCl 2, 25 mM NaHCO3, 1.1 mM MgSO4, 1.2 mM KH2PO4, and 5.6 mM glucose for 1 h under resting tension of 5 g. In all studies, arterial rings were depolarized with KCl (120 mM) containing Krebs bicarbonate buffer and then the rings were equilibrated with Krebs-bicarbonate buffer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation